2020
DOI: 10.18510/hssr.2020.8217
|View full text |Cite
|
Sign up to set email alerts
|

Succession Process in the Family Business: A Case Study of Pekalonganese Batik Cloth Enterprises, Indonesia

Abstract: Purpose: The main purpose of this study is to explain the role of parents in teaching business management to their children from an early age for the success of family business succession. Methodology: It was a qualitative study and data were collected by observation, in-depth interviews, and documentation. The focus of this study was the succession process of the PekalonganBatik business analyzed from the entrepreneurial learning perspective. Interview questions focused on entrepreneurial learning and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Kusumantoro and friends in their research on Batik entrepreneurs in Pekalongan also found that succession planning was carried out by parents by involving their children from childhood in the business processes of family companies, both in terms of production and management by involving them little by little in the company's operational activities (Kusumantoro et al, 2020). While Umans' research from inter-generational relationship's point of view found that the higher the quality of relationship between predecessor and successor the more it strengthens positive effects of the succession intention on the succession planning level (Umans et al, 2019).…”
Section: Succession Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Kusumantoro and friends in their research on Batik entrepreneurs in Pekalongan also found that succession planning was carried out by parents by involving their children from childhood in the business processes of family companies, both in terms of production and management by involving them little by little in the company's operational activities (Kusumantoro et al, 2020). While Umans' research from inter-generational relationship's point of view found that the higher the quality of relationship between predecessor and successor the more it strengthens positive effects of the succession intention on the succession planning level (Umans et al, 2019).…”
Section: Succession Planningmentioning
confidence: 99%
“…Employees who work on a complex series of batik processes will also be included in those who will be transferred to successors. Not to forget, people who have become customers of family batik, become part of the legacy that is passed on by successors (Kusumantoro et al, 2020). Not only tangible inheritance is passed down, no less important is intangible abilities such as passion and other soft skills required, namely the ability to innovate, communicate and negotiate, make decisions (Duh, 2014).…”
Section: Succession Processmentioning
confidence: 99%
“…The batik business is generally managed by family members up to several generations, either by immediate family or extended family. All business activities of the Chinese community are closed, so that non-family members are omitted (Kusumantoro et al, 2020;Sharma et al, 1997).…”
Section: Batik As a Legitimacy Of Chinese Community Assetsmentioning
confidence: 99%